FORMS AND COMPONENTS OF MATERIAL INCENTIVES FOR TOP-MANAGERS OF THE ENTERPRISES - SAVITSKA, OLHA; SHCHUR, O.; NEGRYCH, O. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Tools for material incentives for senior management remain an important and effective element of motivation. It is necessary to take into account the dependence of the company's performance and the achievement of high efficiency indicators on the level of material incentives for managers. The question of forming the optimal balance between the form, type and amount of remuneration of the top-managers and the results of their activities are relevant, to which there is still no unambiguous answer and scientists are actively discussing their solution. The article highlights the need to pay a fixed remuneration to managers in combination with a variable part, which will depend on the results of activities and will encourage managers to work for the result. In addition, establishing material remuneration requires taking into account the level of personal and professional qualities of the top-managers compared to other employees. The role of incentive tools is great, and it is necessary to balance material and intangible incentives in accordance with the capabilities and needs of the top-managers. The main differences between top-managers and employees are considered, which are proposed to be taken into account when developing a system of material incentives for top-managers of the enterprise. The components of material incentives for top-managers are highlighted. According to the results of scientific research, the classification of forms of material incentives for top-managers has been improved according to the following classification features: by method, form, salary structure, subject composition, degree of security, time of validity, basis of payment, source of income, results of work. The article also emphasizes the importance of material incentives of innovative activity of top-managers and a combination of material and intangible forms of labor incentives. A successful combination of material and intangible forms of incentives will effectively allow to use the potential of managers to achieve the company's goals.
Keywords: stimulation; motivation; material incentives; intangible incentives; top-manager; reward; compensation (social) package; “golden parachute”